2006
DOI: 10.4314/ajfand.v6i1.19168
|View full text |Cite
|
Sign up to set email alerts
|

Improvement and popularization of diversified cassava products for income generating and food security: a case study of Kibabu

Abstract: Kibabu is a traditional, plain, deep fried cassava product prepared from cassava paste. It was noticed in Muheza district, Tanzania, to be nutrient-deficient as it was prepared from plain cassava that was only mixed with onions, and then deep fried. There was also room to improve its acceptability for wider dissemination. A study was conducted to improve nutrient content and palatability of traditional kibabu, using 80 % cassava and other staple mixture and 20 % onion-garlic (flavour improver). Laboratory anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…The study observed that most people preferred boiled fufu to stirred fufu. This result agrees with results of Laswai et al (2005) and Silayo et al (2004) who found that the high-quality boiled cassava products were mostly preferred by people. Though the study observed that majority of the respondents stated that stirred fufu is easier to prepare and has higher quality.…”
Section: Consumers' Preferences On Boiled and Stirred Fufusupporting
confidence: 93%
“…The study observed that most people preferred boiled fufu to stirred fufu. This result agrees with results of Laswai et al (2005) and Silayo et al (2004) who found that the high-quality boiled cassava products were mostly preferred by people. Though the study observed that majority of the respondents stated that stirred fufu is easier to prepare and has higher quality.…”
Section: Consumers' Preferences On Boiled and Stirred Fufusupporting
confidence: 93%
“…In this respect, cassava processing could be related to the necessity of having permanent food reserves and also to remove toxic cyanide glucoside contained in its edible organs before its consumption. Apart from overcoming the perishability and toxicity of the crop, transformation has also been shown to enhance the nutritional standard, along with adding substantial economic value to cassava (Laswai et al, 2006;Khampa and Wanapat, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ubi kayu atau singkong (Manihot esculenta Crantz sin) merupakan tanaman semusim dan masih satu famili dengan tanaman karet. Kelebihan tanaman ubi kayu yaitu dapat tumbuh meski ditanam pada kondisi dan iklim yang kurang baik, tetap mampu tumbuh pada tanah yang kurang atau tidak subur, memiliki rentang panen yang cukup panjang (10-30 bulan), sumber pangan pokok terbesar setelah gandum, beras dan jagung (Laswai et al, 2006;Vessia, 2007). Nasi tiwul merupakan salah satu alternatif olahan pangan dari umbi singkong, pada penelitian ini diharapkan tiwul dapat menggantikan beras sebagai bahan pangan pokok masyarakat Indonesia.…”
Section: Pendahuluanunclassified